Plasma ACTH Precursors measured by Pro-opiomelanocortin (POMC) ELISA as a Predictor of Silent Corticotroph Adenomas - Alison Garber; Gabrielle Page-Wilson; Yu Sun; Peter Canoll; Jeffrey N Bruce; Zhezhen Jin; Alexander G Khandji; Sunil Panigrahi; Anne White; Leanne Walker; Sharon L Wardlaw; Pamela U Freda (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Background Silent corticotroph adenomas (SCAs) are only identified after surgical removal and pathological analysis. Defective processing of pro-opiomelanocortin (POMC) may underlie these tumors’ failure to secrete biologically active ACTH. While prior studies found elevated plasma POMC in patients with Cushing disease (CD) due to macroadenomas and ectopic ACTH-secreting tumors, plasma POMC has not been measured in a clinically non-functioning pituitary adenoma (CNFPA) cohort. We hypothesized that elevated plasma POMC could serve as a marker of the SCA sub-type of CNFPAs. Methods We measured plasma POMC levels in 264 CNFPAs in a prospective, observational study (157 treated surgically and 107 observed without surgery), 10 known SCAs, and 3 patients with CD using a POMC 2-site ELISA that detects POMC and pro-ACTH but not ACTH. Surgically removed tumors underwent immunohistochemistry to classify them into SCA and Not SCA subtypes. Normal POMC levels were < 39 fmol/mL. Results POMC levels were higher in SCA (n = 7) than Not SCA (n = 138) groups (median 73 vs. 14 fmol/mL, p < 0.001) and elevated (≥ 39 fmol/mL) in 85.7% of SCAs. Elevated POMC predicted SCA presence amongst CNFPAs with a sensitivity of 85.7% and specificity of 97.9%. POMC was elevated in all known SCAs with visible residual tumor, ranging from 49.6 to 3796 fmol/mL. Conclusion We found plasma POMC level to be a promising predictor of SCA presence in a CNFPA cohort. POMC measurement could become part of the initial CNFPA evaluation and used for monitoring for residual and recurrent tumor after surgery. These preliminary findings warrant further investigation.